PERAN PENDIDIKAN PANCASILA SEBAGAI PEMBENTUK KARAKTER PADA PESERTA DIDIK SEKOLAH DASAR - Mimin Ninawati; Alfia Dwi Saputri; Jihan Puspa Rani; Rizkia Amelia; Shalma As’ari; Silvia Mulyana Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education has a strategic role in shaping the character and personality of the younger generation as the nation's successors. In the Indonesian context, Pancasila education is one of the main pillars in realizing this goal. As a national ideology, Pancasila is not only the basis of the state, but also the values that are internalized in various aspects of life, including the field of education. And Pancasila education also has an important role in shaping the character of students, namely at the elementary school (SD) level. Pancasila education has great potential to shape the character of students in elementary schools. Through this education, it is hoped that Indonesia's young generation will not only be intellectually intelligent, but also have strong character, full of integrity, and can become good and responsible citizens. As the basis of the state and the nation's way of life, Pancasila contains noble values that can shape the attitudes and behavior of students in accordance with the moral values that apply in Indonesian society. Pancasila education also functions to increase students' understanding of the importance of living together in diversity and tolerance, which is very relevant in Indonesia's multicultural social context. This article aims to examine how Pancasila education is implemented in elementary schools in order to shape students' character based on Pancasila values, such as mutual cooperation, social justice, and respect for diversity. Using a qualitative approach, this research reveals that the integration of Pancasila values in the curriculum and extracurricular activities can increase understanding and application of positive attitudes that support character formation. Instilling these values not only equips students with knowledge, but also life skills that are useful for forming individuals with integrity, tolerance and responsibility. Therefore, Pancasila education in elementary schools has a strategic role in creating a young generation capable of maintaining national unity and integrity.